1984
DOI: 10.1002/spe.4380140607
|View full text |Cite
|
Sign up to set email alerts
|

Automatic generation of make dependencies

Abstract: In the UNIX environment, it is standard practice to use the make program to keep a system of interrelated modules up to date. When text files contain so‐called include statements referring to additional text files whose contents are to replace the statements, it soon becomes impractical, in a growing system, to manually maintain all make dependencies implied by these references. Therefore, the dependencies are often generated automatically from extracted include statements by various methods. However, the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Based on pattern matching, simple methods have been developed for generating Make descriptions of such dependencies. 33 A class of tools have been developed that exploit such methods and feature automatic generation of Makefiles or provide information necessary to maintain them. Most of these tools support Makefile descriptions for C and are based on the C preprocessor macro language.…”
Section: Coarse Granularity Methods and Toolsmentioning
confidence: 99%
“…Based on pattern matching, simple methods have been developed for generating Make descriptions of such dependencies. 33 A class of tools have been developed that exploit such methods and feature automatic generation of Makefiles or provide information necessary to maintain them. Most of these tools support Makefile descriptions for C and are based on the C preprocessor macro language.…”
Section: Coarse Granularity Methods and Toolsmentioning
confidence: 99%
“…Essentially the method is to scan source files for dependent-on files, assuming compliance with suffix conventions for C, yacc, etc. Walden's [14] analysis showed that a number of tools did not generate (in our terminology) complete rules for targets with dependencies that were derived targets. Our notion of build rules supplements Walden's work because our notion of (rule) completeness is defined formally and independently of C, and so provides a stronger basis for arguing the correctness of makefile generators based on, say, the rectified algorithm proposed by Walden.…”
Section: Derivabilitymentioning
confidence: 99%
“…In restrospect it can be seen that Stuart Feldman's original paper on make [3] tacitly assumed that makefile rules satisfy properties that guarantee safeness. Walden [14] pointed to errors in makefile generators for C and related tools, in particular in rules whose dependencies were derived files (as opposed to source files), and proposed new algorithms for such generators.…”
Section: Introductionmentioning
confidence: 99%